Heterotopic Pregnancy after a Spontaneous Conception: A Case Report - Hartanto, Amadea Ivana; Siddiq, Amillia; Erfiandi, Febia (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Introduction: Heterotopic pregnancy (HP) is a rare and potentially life-threatening condition in which an intrauterine pregnancy (IUP) and an ectopic pregnancy (EP) occur simultaneously. Increased awareness and early diagnosis are crucial to preventing complications. This case highlights the importance of timely identification and appropriate management of heterotopic pregnancy.Case report: A 32-year-old G2P1A0 pregnant woman was referred with a suspicion of heterotopic pregnancy. The patient had no prior complaints and had a spontaneous conception, there was no history of in vitro fertilization. At 2 months of gestation, an ultrasound revealed both an intrauterine pregnancy and an ectopic pregnancy. The laparoscopic diagnostic evaluation confirmed an enlarged right horn, requiring a wedge resection of the right horn. The procedure was completed successfully, and the intrauterine pregnancy progressed until term. This resulted in a cesarean section delivery of a healthy female infant weighing 3000 grams.Conclusion: This case underscores the need for a high index of suspicion when diagnosing heterotopic pregnancy, even in asymptomatic patients. Early recognition and surgical intervention significantly improve outcomes. The findings offer valuable insights for clinical practice and highlight the importance of vigilance in the evolving landscape of reproductive medicine.Kehamilan Heterotopik Pasca Konsepsi Spontan: Sebuah Laporan KasusAbstrakPendahuluan: Kehamilan heterotopik (KH) adalah kondisi langka dan berpotensi mengancam jiwa ketika kehamilan intrauterin (KIU) dan kehamilan ektopik (KE) terjadi secara bersamaan. Kesadaran yang lebih tinggi dan diagnosis dini sangat penting untuk mencegah komplikasi. Kasus ini menyoroti pentingnya identifikasi yang tepat waktu dan manajemen yang sesuai dari kehamilan heterotopik.Laporan kasus: Seorang wanita hamil G2P1A0 berusia 32 tahun dirujuk dengan kecurigaan kehamilan heterotopik. Pasien tidak memiliki keluhan sebelumnya dan kehamilan terjadi secara spontan, tanpa riwayat fertilisasi in vitro (IVF). Pada usia kehamilan 2 bulan, pemeriksaan ultrasonografi menunjukkan adanya kehamilan intrauterin dan kehamilan ektopik. Evaluasi diagnostik laparoskopi mengonfirmasi adanya pembesaran tuba kanan sehingga dilakukan reseksi parsial tuba kanan. Prosedur ini berhasil diselesaikan sampai kehamilan intrauterine cukup bulan dan menghasilkan kelahiran bayi Perempuan sehat dengan berat 3000 gram melalui operasi sesar.Kesimpulan: Kasus ini menekankan perlunya tingkat kecurigaan yang tinggi dalam mendiagnosis kehamilan heterotopic termasuk pada pasien yang tidak bergejala. Pengenalan dini dan intervensi bedah secara signifikan meningkatkan hasil klinis. Temuan ini memberikan wawasan berharga untuk praktik klinis dan menyoroti pentingnya kewaspadaan dalam perkembangan ilmu kedokteran reproduksi.